Perceptions of general practitioners towards the services provided by advanced practice nurses: a cross-sectional survey in France - Charles Goddaert; Pierre-Antoine Gérard; Charlotte Kessler; Mélaine Leblanc; Coralie Barbe; Jan Chrusciel; Clément Cormi; Stéphane Sanchez (BMC, 2023)
Abstract Background New healthcare professions are emerging due to scarce medical resources. The appearance of a new healthcare profession, advanced practice nurses (APNs), has raised questions about how general practitioners interrelate with them as primary care providers. The objective of this study was to explore the perceptions general practitioners have towards the services rendered by APNs to patients, to general practice and the role they play in the healthcare system. Methods A survey-based, cross-sectional study was conducted throughout the Grand Est region of France which covers 57,333km2 and has a population of approximately 5,562,651. The survey was compiled using pre-existing questionnaires and was carried out from July to September 2022 via email. Variables collected were rate of acceptability and socio-demographic characteristics. Results In total, 251 responses were included. The mean age of general practitioners was 41.7 years, most were women (58.2%) and worked in rural areas of the region (53.8%). Over 80% of respondents practiced in group structures (defined as either multi-professional health centers (n = 61) or in group practices (n = 143)). Most respondents (94.0%) were familiar with the APN profession and did not consider that APNs improved access to care (55.8%, percent of responders with score ≤ 3/10). Moreover, most did not believe that APNs were useful as a primary care provider for patients (61.8%). However, being a member of a territorialized healthcare community, known as Communautés Professionnelles Territoriales de Santé (CPTS), was associated with a positive appraisal of APNs' services (OR = 2.116, 95%CI: 1.223 to 3.712; p = 0.007). Conclusions Encouraging shared and networked practice within a healthcare community may promote a positive perception of new actors. Further studies need to be conducted to show whether the integration of APNs into healthcare networks improves quality of care.